Cell typing of biological heart valves prosthesis explanated due to the development of calcium-associated dysfunctions - R. A. Mukhamadiyarov; N. V. Rutkovskaya; S. G. Rutkovskaya; Yu. N. Odarenko; I. V. Mil’to; L. S. Barbarash (Бюллетень сибирской медицины, 2018)
Purpose. To perform immunohistochemical typing of cells obtained from calcinated biological heart valve prosthesis removed during reoperations.Materials and methods. We investigated 19 models (“KemCor” and “PeriCor”) of biological heart valve prosthesis produced by NeoCor Company (Kemerovo, Russia) and removed from the mitral position due to the development of primary tissue inconsistency with calcification. The following markers were used for immunohistochemical cells typing in the analyzed samples: CD3 (T-lymphocytes), CD20 (B-lymphocytes), CD34 and VEGFR2 (endotheliocytes), CD68 (monocytes/macrophages), vimentin (fibroblasts), and α-smooth muscle actin (smooth myocytes).Results. Uneven distribution and wide variety of intercellular interactions, as well as contacts with matrix components and mineral deposits, were observed. In case of endotheliocytes (CD34 and VEGFR2 positive cells) two types of localization were described. In the first variant, they formed a monolayer on the surface of biological prosthesis flaps; in the second variant, they were a part of capillary-like structures in the surface of the xenomaterial. CD68 positive cells were found both in a surface and in deep layers of the samples. Near such cells fragmentation and stratification of collagen fibers with the formation of fine-fibrous cellular networks were detected. Vimentin-positive cells (fibroblasts) were located in groups or singly in the sites of destruction of the connective tissue and took part in the formation of a new matrix. The density of α-smooth muscle actin-positive cells, morphologically identical to myocytes, was high in the surface of biological prosthesis flaps and low in the deeper layers. CD3 and CD20 positive cells related to T- and B-lymphocytes, respectively, were represented by the single cells in most of analyzed samples.Conclusions. Maintaining of the structural and functional integrity of biological heart valve prosthesis, in addition to the characteristics of the implantable devices, defines a complex of recipient factors, including not only mechanical damage during operation, but also various immune and cellular mechanisms.